سلطة القاضي الاستعجال الإداري في فرض الغرامة التهديدية - شتيوي, صليحة; بوعيشة, خديجة (My University, 2020)
الغرامة التهديدية هي وسيلة لحث الإدارة على التنفيذ الأحكامالإدارية؛ ففي حالة عدم التنفيذ الكلي أو الجزئي أو التأخير في تنفيذ أمر أو قرار نهائي، يجوز للقاضي الاستعجال الإداري أن يأمر بغرامة التهديدية لجبر الإدارة على تنفيذ التزاماتها، وإذا استمرت هذه الأخيرة في عدم التنفيذ، يمكن للقاضي الاستعجال الإداريالأمر بالتصفية الغرامة التهديدية التي كرسها المشرع في المادة الإدارية وفقا لأحكام قإمإ.فالغرامة التهديدية إذن هي وسيلة فعالة بيد القاضي الاستعجال الإداري لإجبار الإدارات العامة المتقاعسة في التنفيذ على احترام أحكام القضاء الصادرة باسم الشعب.Fine menacing is mean used to induce the administration to execute judicial decisions or judgements. When the administration refuses to execute judicial judgment. Administrative emergency judge may decide a fine menacing to oblige the administration to implement its obligation. If administrative emergency judge may decide the fine menacing according to the civil and administrative proceeding. Thus, fine menacing is an effective measure which the administrative emergency judge uses to induce the administration to respect judgment.
مذكرة ماستر
Keywords: الغرامة التهديدية - الأحكام الإدارية – قانون الإجراءات المدنيةوالإدارية – قاضي الاستعجال الإداري – التنفيذ الجبري; Threatening fine - Administrative rulings - Civil and administrative procedures law - Administrative emergency judge - Forced execution